Parallel gradients in FENO and in the prevalences of asthma and atopy in adult general populations of Sweden, Finland and Estonia — A Nordic EpiLung study. (November 2020) - Lassmann-Klee, Paul G.; Piirilä, Päivi L.; Brumpton, Ben; Larsson, Matz; Sundblad, Britt-Marie; Põlluste, Jaak; Juusela, Maria; Rouhos, Annamari; Meren, Mari; Lindqvist, Ari; Kankaanranta, Hannu; Backman, Helena; et al.
Abstract: The prevalence of asthma is higher in Sweden and Finland than in neighbouring eastern countries including Estonia. Corresponding difference in bronchial eosinophilic inflammation could be studied by F ENO measurements. We aimed to compare F ENO in adult general populations of Sweden, Finland, and Estonia, to test the plausibility of the west-east disparity hypothesis of allergic diseases. We conducted clinical interviews (N = 2658) with participants randomly selected from the general populations in Sweden (Stockholm and Örebro), Finland (Helsinki), and Estonia (Narva and Saaremaa), and performed F ENO ( n  = 1498) and skin prick tests (SPT) in 1997–2003. The median (interquartile range) of F ENO (ppb) was 15.5 (9.3) in Sweden, 15.4 (13.6) in Finland and 12.5 (9.6) in Estonia. We found the lowest median F ENO values in the Estonian centres Saaremaa 13.1 (9.5) and Narva 11.8 (8.6). In the pooled population, asthma was associated with F ENO ≥25 ppb, odds ratio (OR) 3.91 (95% confidence intervals: 2.29–6.32) after adjusting for SPT result, smoking, gender and study centre. A positive SPT test increased the likelihood of asthma OR 3.19 (2.02–5.11). Compared to Saaremaa, the likelihood of having asthma was higher in Helsinki OR 2.40 (1.04–6.02), Narva OR 2.45 (1.05–6.19), Örebro OR 3.38 (1.59–8.09), and Stockholm OR 5.54 (2.18–14.79). There was a higher prevalence of asthma and allergic airway inflammation in adult general populations of Sweden and Finland compared to those of Estonia. Atopy and elevated F ENO level were independently associated with an increased risk of asthma. In conclusion, the findings support the earlier west-east disparity hypothesis of allergic diseases. Highlights: F ENO can measure eosinophilic airway inflammation in asthma. Asthma prevalence and risk varies between countries due to differences in risk factors. Populations in Sweden and Finland have a higher asthma risk than in Estonia. The findings support the west-east disparity hypothesis of allergic diseases. Atopic sensitisation increases the risk of asthma.